Anion-mediated solvation structures and intercalation chemistry of aqueous zinc-ion electrolytes - Shiqiang Wei; Quan Zhou; Shuangming Chen; Yixiu Wang; Pengjun Zhang; Wei Jiang; Changda Wang; Jiewu Cui; Xiaojun Wu; Li Song (Proceedings of the National Academy of Sciences, 2026)
Understanding solvent/solute-borne coordination structures and their impact on electrode intercalation chemistry is crucial for the rational design of high-performance electrolytes. Nevertheless, the anion coordination mechanisms governing solvation structures and their influence on electrochemical properties within aqueous zinc-ion electrolytes remain insufficiently explored. In this work, we systematically elucidate the Zn 2+ coordination environments in dilute aqueous zinc-ion electrolytes containing three different Zn salts (Zn(OTf) 2 , ZnCl 2 , and Zn(Ac) 2 ) using X-ray absorption fine structure (XAFS) spectroscopy and metadynamics simulations. Our results identify distinct average Zn 2+ coordination species: [Zn(H 2 O) 6 ] 2+ in Zn(OTf) 2 , [Zn(H 2 O) 5 Cl] + in ZnCl 2 , and [Zn(H 2 O) 4 (Ac)] + in Zn(Ac) 2 . Further employing synchrotron-based spectroscopy and in situ synchrotron radiation X-ray diffraction (SRXRD), we reveal that the electrode operating in Zn(OTf) 2 electrolyte exhibits minimal crystal lattice distortion upon Zn 2+ de/intercalation cycling, thereby delivering highly reversible electronic structure evolution and zinc-ion electrochemistry. In stark contrast, pronounced structural shape-shifting is observed in ZnCl 2 and Zn(Ac) 2 electrolytes, attributed to electrode dissolution and acetate anion coinsertion, respectively. These processes induce significant structural deterioration during cycling and compromise electrochemical reversibility. This study provides critical insights into the anion coordination chemistry within aqueous electrolytes and its profound influence on electrode intercalation behaviors, offering essential guidance for developing advanced high-performance aqueous batteries.